2012
DOI: 10.1176/appi.ps.201000405
|View full text |Cite
|
Sign up to set email alerts
|

Service Utilization by Hospitalized Suicide Attempters With Schizophrenia or Depression in Montreal

Abstract: The publicly managed health and social services system in Montreal seems to respond rather well to severe suicide attempts, including those by men with a concurrent substance use disorder known to be at high suicide risk. However, better coordination among hospital emergency departments, primary care, specialized mental health services, and addiction services is needed in order to enhance continuity of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Better case identification from administrative databases would enhance our ability to assess the quality of suicide management and risk of recurrence that requires case audit and health services utilisation assessments. 53,54 In conclusion, our study showed that about half of individuals who seek medical care for attempted suicide are admitted to hospital. About half of attempters use poisoning as a method of suicide, and a quarter do not have a history of mental disorders.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Better case identification from administrative databases would enhance our ability to assess the quality of suicide management and risk of recurrence that requires case audit and health services utilisation assessments. 53,54 In conclusion, our study showed that about half of individuals who seek medical care for attempted suicide are admitted to hospital. About half of attempters use poisoning as a method of suicide, and a quarter do not have a history of mental disorders.…”
Section: Discussionmentioning
confidence: 70%
“…Better case identification from administrative databases would enhance our ability to assess the quality of suicide management and risk of recurrence that requires case audit and health services utilisation assessments. 53,54…”
Section: Discussionmentioning
confidence: 99%
“…In the identified studies, older age was generally associated with higher self-reported service use among people with suicidality (Ahmedani et al, 2012; De Leo, Cerin, Spathonis, & Burgis, 2005; Encrenaz et al, 2012). Females were more likely to talk about suicidal ideation to health professionals (Encrenaz et al, 2012) and use health services (Ahmedani et al, 2012; De Leo et al., 2005; Routhier, Leduc, Lesage, & Benigeri, 2012; Wong, Brownson, Rutkowski, Nguyen, & Becker, 2014) than males were. Individuals of ethnic minorities including Latino (Ahmedani et al, 2012; Downs & Eisenberg, 2012; Freedenthal, 2007; Meyer, Teylan, & Schwartz, 2015; Wu, Katic, Liu, Fan, & Fuller, 2010), Black (Ahmedani et al, 2012; Freedenthal, 2007; Meyer et al, 2015; Wu et al, 2010), and Asian (Ahmedani et al, 2012; Downs & Eisenberg, 2012; Wong et al, 2014) tended to have less help-seeking behavior compared with Caucasian.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of mental health issues such as depression (Ahmedani et al, 2012; Arria et al, 2011; Encrenaz et al, 2012; Husky et al, 2012; Vasiliadis, Gagne, Jozwiak, & Preville, 2013; Wu et al, 2010), anxiety (Ahmedani et al, 2012; Arria et al, 2011; Encrenaz et al, 2012; Wu et al, 2010), and substance use (Encrenaz et al, 2012; Freedenthal, 2007; Routhier et al., 2012) was associated with greater help-seeking behavior among people with suicidality. In addition, severe suicidal intent (De Leo et al, 2005; Wong et al, 2014), history of suicidal ideation (Husky et al, 2012; McKibben et al, 2014; Pagura, Fotti, Katz, Sareen, & Tea, 2009), suicidal plans (Encrenaz et al, 2012; Husky et al, 2012), and suicidal attempts (Ballard et al, 2014; De Leo et al, 2005; Encrenaz et al, 2012; Freedenthal, 2007; McKibben et al, 2014; Milner & De Leo, 2010; Pagura et al, 2009) also facilitated help-seeking behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This is the responsibility of each individual Canadian province and territory, and there is no overarching federal authority. 55 Other countries with similar health care systems and access to large health administrative databases, such as the United Kingdom, 13 have begun to examine the associations of mental health care services with suicide and how the innovative use of these data sources may improve prevention strategies. Moreover, a national registry database in Norway has been incorporated by the Norwegian Public Health Institute as part of the effort to monitor mental health and suicidal behaviour.…”
Section: Ethics In the Canadian Context: Respecting Access To Documenmentioning
confidence: 99%